Sleep Characteristics of Pediatric Burn Patients - Esra Ardahan Akgül; Hatice Yıldırım Sarı (Galenos Yayinevi, 2019)
Aim:Soft tissue injuries which happen because of high heat, chemicals etc. are called burns. Sleep is a complex behavior regulated by the interaction of anatomical and neurochemical areas in the central nervous system. After being burnt; patients are exposed to many stressors that cause sleep interruption and decrease sleep quality. The purpose of this study was to determine sleep characteristics, sleeplessness and sleep habits in pediatric burn patients.Materials and Methods:This descriptive study was carried out on 96 children who were 2-6 years old in the pediatric surgery department/burn unit for a period of between 2-7 days. For data collection, a demographic data collection form and a sleep problems characteristics and identification survey, which was created by the researchers, were used. Data were collected via face to face interviews with mothers. Questions were asked in order to compare pre- and post- burn sleep quality.Results:Of the children, 53.1% were male and their mean age was 3.36±1.39 years. There was a significant difference between pre- and post- burn periods on children's sleeping and waking hours, total and night sleep duration, total daily sleep duration, existence of sleep interruption and number of interruptions, trouble of falling asleep and sleep latency, being tired in the morning, forcing the children to wake up and also the duration of waking up.Conclusion:With the knowledge about the importance of sleep, attention should be paid to the sleep of children that we are providing care to. Supportive environmental regulations should be made to improve the quality of sleep in hospitals.